The Role of Moisturizers in Maintaining Skin Barrier Function in a Desert Climate: A Comparative Study in Dubai and a Temperate Region - Franklin Shane (Scientific Journal of Dermatology and Venereology, 2023)
Introduction: Desert climates present unique challenges to skin health due to low humidity, high temperatures, and intense sun exposure, potentially compromising the skin barrier. Moisturizers play a crucial role in mitigating these effects. This study investigates the impact of moisturizers on skin barrier function in individuals residing in Dubai (desert climate) and a temperate region. Methods: A cross-sectional study was conducted involving 100 participants (50 from Dubai, 50 from a temperate region). Skin barrier function was assessed using transepidermal water loss (TEWL) measurements and stratum corneum hydration levels. Participants' moisturizer usage patterns and perceived skin dryness were recorded. Results: Dubai residents exhibited significantly higher TEWL values and lower stratum corneum hydration levels compared to those in the temperate region, indicating a compromised skin barrier. Regular moisturizer use was associated with significantly improved skin barrier function in both groups, with a more pronounced effect observed in Dubai residents. Conclusion: This study highlights the vulnerability of skin barrier function in desert climates. Regular moisturizer use effectively improves skin barrier function, particularly in arid environments. These findings underscore the importance of moisturizers as a cornerstone of skincare in desert climates.